Study of the economic involvement of civil organizations - Pierog, Anita (Acta Agraria Debreceniensis, 2013)
On the basis of definitions found in the literature, as well as my own, civil organizations are such structures that basically have specific organizational characteristics and their own management tasks in view of their operational principles.In my study, I describe the status quo of civil organizations, as regards their “economic involvement”. On this basis, I examined the level of the economic involvement of civil organizations, more specifically as to the level of economic partnership between representatives of civil organizations and greater society. I placed the economic involvement of civil organizations into three categories: ‘active’, ‘passive’ and ‘has no effect on individuals in society’. During my research, I largely build my investigations on the results I obtain through questionnaires, which I measure on a representative sample. On the basis of this sampling, the County Court of Justice was able to launch its own website. Thus, my research on this topic included the townships in Hajdú-Bihar County.The results of my research arise from an analysis of data I collected in 2010–2011. This data allowed me to be able to make several observations concerning the specific activities of civil organizations. I have result of the organizations’ annual income, as well as the types of revenues they obtain the county. The results of my analysis of the examined organizations show that more than two-thirds (66.7%) of their available revenues totaled less than one million Hungarian Forints, with no significant difference in the amount of revenue existing between the two organizational types (association, foundation). The most common source of revenue claimed by the studied organizations was from membership fees and/or various types of funding programs. In examining civil organizations on the basis of their type, I made the observation that in the case of associations, it was the membership fees which were the most characteristic type of income, followed by the 1% donation possibility from personal income tax filings for foundations, but funding proposal possibilities were also important for both types of organization.